Endovascular treatment of pulmonary sequestration with thoracic endograft: Two case reports. Issue 31 (August 2019) - Chen, Yu; Liu, Bao; Shao, Jiang; Liu, Duan; Zheng, Yuehong
Abstract: Introduction: Pulmonary sequestration (PS) is a rare congenital lung malformation. The classical treatment of the disease has been conventional surgery with resection of abnormal parenchyma. Recently, the endovascular embolization has been proposed for the treatment of this disease. Here we present 2 cases of PS successfully treated with thoracic endograft. Patient concerns: Two patients with abnormal consolidation in the left lower lobe were admitted in our hospital. Diagnosis: Chest computed tomography angiography (CTA) showed abnormal consolidation in the left lower lobe, which received systemic blood supply from the descending aorta in both patients. So the diagnosis of PS was confirmed. Interventions: Endovascular treatment with thoracic endograft was successfully performed. Outcomes: The patients recovered well and were completely free of symptoms. And the CTA follow-up showed the abnormal pulmonary parenchyma shrunk significantly. Conclusions: Endovascular treatment with thoracic endograft is a promising treatment option for PS.